Ising model in a light-induced quantized transverse field - Jonas Rohn; Max Hörmann; Claudiu Genes; Kai Phillip Schmidt (Physical Review Research, 2020)
We investigate the influence of light-matter interactions on correlated quantum matter by studying the paradigmatic Dicke-Ising model. This type of coupling to a confined, spatially delocalized bosonic light mode, such as provided by an optical resonator, resembles a quantized transverse magnetic field of tunable strength. As a consequence, the symmetry-broken magnetic state breaks down for strong enough light-matter interactions to a paramagnetic state. The nonlocal character of the bosonic mode can change the quantum phase transition in a drastic manner, which we analyze quantitatively for the simplest case of the Dicke-Ising chain geometry. The results show a direct transition between a magnetically ordered phase with zero photon density and a magnetically polarized phase with superradiant behavior of the light. Our predictions are equally valid for the dual quantized Ising chain in a conventional transverse magnetic field.